1997
DOI: 10.1139/z97-035
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric comparisons of skulls of harbour porpoises (Phocoena phocoena) from the Baltic, Kattegat, and Skagerrak seas

Abstract: The population structure of harbour porpoises (Phocoena phocoena) in Swedish waters was studied by means of morphometric comparisons of skulls from 103 specimens. The study was designed to investigate whether harbour porpoises in the Baltic Sea form a distinct population separate from animals found in the Kattegat and Skagerrak seas. The Kattegat–Skagerrak (K-S) sample was divided into summer and winter samples to account for possible migrational movements by Baltic Sea animals between breeding seasons. Both m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…In contrast, previous studies achieved ≤ 72% correct classification (e.g. Börjesson & Berggren 1997). It has been documented that diet was significantly correlated with adaptive morphological features (e.g.…”
Section: Morphologymentioning
confidence: 72%
“…In contrast, previous studies achieved ≤ 72% correct classification (e.g. Börjesson & Berggren 1997). It has been documented that diet was significantly correlated with adaptive morphological features (e.g.…”
Section: Morphologymentioning
confidence: 72%
“…Harbor seals in the Moray Firth changed from a diet of mainly sand eels in quarters 2 and 3 to other species (including gadids and clupeids) in quarters 1 and 4 (Pierce et al 1991, Tollit andThompson 1996). Borjesson and Berggren (1996) found that herring was the main prey of harbor porpoises in Swedish waters all year round, but the contribution of sprat and whiting to the diet varied seasonally. Gannon et al (1998) reported that herring was the main prey of harbor porpoises in the Gulf of Maine in both summer and autumn, but was more important in the summer diet while silver, red, and white hakes and pearlsides were more important in the autumn diet.…”
Section: Seasonal Variation In Dietmentioning
confidence: 99%
“…Three harbor porpoise populations have been proposed to inhabit the waters between the North Sea and the Inner Baltic Sea; the North Sea/Skagerrak population, the southern Kattegat/BES population, and a population in the IBS, based on morphology and genetic markers (microsatellites and mitochondrial DNA) [3236]. The most recent large-scale population genetics study [32] indicates subtle population differentiation between the Baltic Sea regions, and partially addresses earlier criticism, which suggested that managing Baltic porpoises as an independent conservation unit is premature [37].…”
Section: Introductionmentioning
confidence: 99%